Fully-printed, all-polymer integrated twilight switch. (21st September 2015) - Dell'Erba, Giorgio; Perinot, Andrea; Grimoldi, Andrea; Natali, Dario; Caironi, Mario
Abstract: In this contribution we demonstrate an integrated photoactive switch employing a fully-printed planar photodetector and complementary Schmitt trigger. A photoactive switch is fundamental to several light driven systems, such as twilight sensors or industrial machinery control devices. This paper explores a fabrication methodology that enables reliable complementary logic building blocks and photodetectors with a fully-printed, all-polymer approach, resulting in a semi-transparent integrated system on a single plastic foil.